Study to assess the compensation and skills of medical library professionals relative to information technology professionals - WEISE, Frieda O; MCMULLEN, Thomas D; GROUP, Hay (Bulletin of the Medical Library Association, 2001)
The study seeks to determine how medical library professionals performing information-technology (IT) roles are compensated and how their positions are designed compared to information technology staff in their institutions. 550 medical library directors in hospital and academic medical libraries were surveyed. The data was then compared to survey data from other compensation studies of the IT industry. There is a gap in compensation between medical library professionals and IT professionals performing similar functions using information technology. Technology-intense library jobs are compensated at higher levels than more traditional jobs. To compete with IT salaries, managers of medical library professionals will need to be ever more cognizant of the employment practices of IT professionals in nonmedical library disciplines. It is typically in the medical library's best interest to ensure that IT-related jobs, accountabilities, and capabilities of the medical library are known and understood by others, especially in the human resources and information technology staff departments.